2014
DOI: 10.1016/j.rgmx.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Análisis genético en APC, KRAS y TP53 en pacientes con cáncer de estómago y colon

Abstract: The APC, KRAS, and TP53 gene mutations were more common in CRC than in SC. Our results suggest the existence of different genetic pathways in the carcinogenesis of SC and CRC and they also reveal a particular mutation frequency in the Colombian patients studied; this could be influenced by factors related to the environment, ethnicity, and lifestyle of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
(73 reference statements)
0
5
0
1
Order By: Relevance
“…A large number studies had suggested that, many gene mutations, such as BRAF, E-Cadherin, and TP53 genes play an important role during the process of cancer development. The synergistic effects of these polymorphisms maybe initiate the procedure of abnormal changes of normal cells, and to accelerate the formation of the tumor solid [3032]. …”
Section: Discussionmentioning
confidence: 99%
“…A large number studies had suggested that, many gene mutations, such as BRAF, E-Cadherin, and TP53 genes play an important role during the process of cancer development. The synergistic effects of these polymorphisms maybe initiate the procedure of abnormal changes of normal cells, and to accelerate the formation of the tumor solid [3032]. …”
Section: Discussionmentioning
confidence: 99%
“…and Venezuela) to 40% (Chile). However, the literature shows that the RAS mutation prevalence usually has a range of 26% to 50% [34][35][36]. Previous studies have shown that mutations in KRAS are variable among populations.…”
Section: Plos Onementioning
confidence: 99%
“…Mutations in APC have been found in several cancers, including colorectal [ 13 ], pancreatic [ 14 ], and hepatocellular [ 15 ], but they are reported to be much rarer in breast cancer. The first report of APC mutations in breast cancer was published by Kashiwaba et al [ 16 ], who detected a mutation rate of 6 % (2 of 31) in primary breast carcinoma samples using PCR followed by restriction fragment length polymorphism (RFLP) and single-strand conformation polymorphism (SSCP) analyses.…”
Section: Discussionmentioning
confidence: 99%